The Most Favourable Selection of the Discrete Model in Fem - Konderla, P. (Engineering Transactions, 1984)
A theorem and proof of the best, in the energetic sense, selection of a discrete model FEM for the linear elasticity problem were presented in the paper. It was proved that the best approximation is obtained if the ratio of the unit elastic strain energy to the density of nodes has a constant value. Proof of the theorem was verified on numerical examples.